Techniques to measure pilus retraction forces - Biais, Nicolas; Higashi, Dustin; So, Magdalene; Ladoux, Benoit (Humana Press Inc., 2012)
The importance of physical forces in biology is becoming more appreciated. Neisseria gonorrhoeaehas become a paradigm for the study of physical forces in the bacterial world. Cycles of elongations and retractions of Type IV pili enables N. gonorrhoeaebacteria to exert forces on its environment, forces that play major roles in the life cycle of this pathogen. In order to better understand the role of these forces, there is a need to fully characterize them. Here, we present two different techniques, optical tweezers and Polyacrylamide MicroPillars (PoMPs), for measuring pilus retraction forces. Initially designed for N. gonorrhoeae, these assays can be readily modified to study other pilus-bearing bacteria including Neisseria meningitidis.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Neisseria; Optical tweezer; PoMPs; Retraction force; Type IV pilus